PERAN KELUARGA DAN GURU DALAM MEMBENTUK MENTAL DAN AKADEMIK ABK - widyasari, surya; nikmatunnur, sholati; yani, linda; ikmal, achmad; Andriani, Opi (Jurnal Pendidikan Vokasi dan Seni, 2025)
To support their mental development, children with special needs (CSN) require specialized care and various strategies. The mental and character development of CSN is significantly influenced by their families and teachers, who help them overcome obstacles in daily life. Children with special needs are involved in daily activities, receive emotional support, and have positive role models within their families. Meanwhile, educators foster effective communication, design flexible curricula, and create inclusive learning environments. The best way to support the development of CSN is through collaboration between teachers and families. The purpose of this article is to analyze these roles and provide practical suggestions for creating a supportive environment.